IDENTIFIKASI PERAN PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP KESEIMBANGAN HIDUP –KERJA - Yuki Fitria (Unib Press Universitas Bengkulu, 2017)
The aim of this study is to identify the influence of perceived organizational support on work-life balance of women employees in banking sector in Padang city. Sample is chosen by using purposive technique with some criteria namely married woman employees and have been employed for 5 or more years. The number of sample was 97. The data used are the primary data that collected through a questionnaire. The resulting data will be analyzed using regression analysis by SPSS. The research shows that, Perceived Organizational Support (POS) has positive and significant influence on female employees work-life balance in banking sector in Padang City.